Kompetensi Dan Spritualitas Gembala Bagi Pertumbuhan Iman Jemaat - Detores, Pernando; Cinta, Yesa (GRAFTA: Journal of Christian Religion Education and Biblical Studies, 2024)
This study discusses the influence of pastoral competence and spirituality on the growth of congregational faith. Pastoral competence includes in-depth theological knowledge, teaching skills, effective leadership, and the ability to manage church services. Meanwhile, pastoral spirituality is related to a consistent prayer life, exemplary Christian character, and willingness to serve with love and sacrifice. This study uses a qualitative approach with an in-depth literature study analysis from various reliable sources related to the topic of pastoral competence and spirituality and its impact on the growth of congregational faith. The purpose of this study is to analyze how pastoral competence and spirituality affect the growth of congregational faith, as well as to provide an understanding of the factors that support the success of pastoral care in the context of the church. The results of this study indicate that both factors have a mutually supportive impact in creating a healthy church environment and building the congregation's faith. Pastors who are competent in teaching and leadership and have a deep spiritual life are able to provide examples that inspire the congregation to grow in faith and actively participate in church services. This study emphasizes the importance of a balance between competence and spirituality in church services to support the overall growth of the congregation's faith.